Test of integrated optical circuits for PON networks - Arantes, João Paulo Gomes (2020)
For the last two decades, the Internet has been target of a technological revolution. The amount of new services and applications that came up with this revolution demanded the search to obtain more bandwidth and bigger data rates. The only technologies capable of satisfying these conditions are the optical communications. The current technology that is capable to satisfying all these needs is the Passive Optical Network(PON). There are some variations of this technology currently being used such as the GPON and EPON. New evolutions of PON are being developed, such as the Next Generation Passive Optical Network 2(NG-PON2) This technology multiplexes different services into separated wavelengths, making its performance more effective. One tool of great matter in this business is the Photonics Integrated Circuit(PIC). The photonic integrated technology has been taking over the conventional optical equipment because it allows the integration of several functionalities into one single chip, saving space and energy. Having in mind the objective of developping next generation optical communication systems, the work presented in this document intends to test PIC in way that they can be used in optical equipment, as for example the Optical Line Terminal(OLT) which has functions of transmitter/receiver situated at the operator's station, and the Optical Network Unit(ONU) situated at the user's location. To make it possible for PIC to be integrated in optical networks these must be tested in order to assure that they perform their functions without any anomalies happening. For such reason, these PIC are at our labs, read to be tested. This work, consisted of the execution of tests to PIC as well as the optimization of the techniques and adequate procedures. In the first place, it is presented an overview of optical networks and PIC. Then the do's and dont's of testing PIC as well as the procedure and preparations of these tests. At last, the tests to the PIC will be performed which represents most of the work shown in this document.